2012
DOI: 10.1158/1078-0432.ccr-11-1716
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Adjuvant Active Specific Immunotherapy Differ between Patients with Microsatellite-Stable and Microsatellite-Instable Colon Cancer

Abstract: Purpose: Active specific immunotherapy (ASI) consisting of an autologous tumor cell vaccine given as adjuvant treatment has been shown to improve recurrence-free survival of patients with colon cancer. The aim of the current retrospective study was to investigate whether the beneficial effects of ASI given as adjuvant treatment correlated with microsatellite instability (MSI), which is considered an important biologic determinant of colon cancer.Experimental Design: Microsatellite status was assessed on archiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…The DSS and RFI data on the 106 patients in the current study are presented in Fig. 2 and are at large in agreement with the data published by us previously on the larger group of 196 patients (28).…”
Section: Patient Characteristics Infiltrating T Cell Numberssupporting
confidence: 92%
See 4 more Smart Citations
“…The DSS and RFI data on the 106 patients in the current study are presented in Fig. 2 and are at large in agreement with the data published by us previously on the larger group of 196 patients (28).…”
Section: Patient Characteristics Infiltrating T Cell Numberssupporting
confidence: 92%
“…Of these 106 tumor samples, 99 were available for CD3 staining and 104 for CD8 staining. (28). The distribution of patient characteristics between the various subgroups was similar to that in the original study reported by Vermorken and colleagues (27).…”
Section: Patient Characteristics Infiltrating T Cell Numberssupporting
confidence: 82%
See 3 more Smart Citations